Synchronous population fluctuations of forest and field voles: implications for population management - Tkadlec, E. (Emil); Suchomel, J.; Purchart, L.; Heroldová, M. (Marta); Čepelka, L.; Homolka, M. (Miloslav) (2011)
Field and forest voles in high population densities cause economic losses. Whereas abundances of the common vole (Microtus arvalis) in the Czech Republic has regularly been checked by the State Phytosanitary Administration for decades, no monitoring program has so far been invented to monitor forest voles. We explored the possibility whether the monitoring data for the common vole can be used to forecast numbers of forest voles. Since 2002, we have monitored (snap trapping) bank vole (Myodes glareolus) populations in three forests situated in southern Moravia, Czech Republic. Correlation analysis of time series of yearly population changes for the common and bank vole revealed that populations of field and forest voles in southern Moravia fluctuate in a close synchrony (correlations higher than 0.8). This result provides the reasonable possibility of exploiting the data from the extensive common vole population monitoring program for prediction in population management of forest voles.